Natural Products that Target the NLRP3 Inflammasome to Treat Fibrosis - Ding, Nan; Wei, Bo; Fu, Xiaohui; Wang, Chuan; Wu, Yimou (Frontiers in Pharmacology, 2020)
Fibrosis is a common pathway followed by different organs after injury, and can lead to parenchymal scarring, cellular dysfunction, and even organ failure. The NLRP3 inflammasome is a multiprotein complex composed of the sensor molecule NLRP3, the adaptor apoptosis-associated speck-like protein containing a CARD (ASC), and the effector protease caspase-1. Overactivation of the NLRP3 inflammasome triggers the abundant secretion of IL-1β and IL-18, induces pyroptosis, and promotes the release of a swathe of proinflammatory proteins, all of which contributes to fibrogenic processes in multiple organs. In recent years, screening bioactive natural compounds for NLRP3 inhibitors to alleviate fibrosis has gained broad interest from the scientific community because of the associated cost-effectiveness and easy access. In this review, we systematically and comprehensively summarize the natural products, including terpenesterpenoids, phenols, and alkaloids, among others and the plant-derived crude extracts, that have been reported to ameliorate fibrosis via inhibiting NLRP3 inflammasome activation and highlight the underlying mechanisms. Among all the compounds, diterpenoids is the most promising candidates for inhibiting NLRP3 inflammasome activation and improving fibrosis, as they possess combined inhibitory effect on NLRP3 inflammasome assembly and NF-κB signaling pathway. All the information may aid in the development of therapeutic strategies for the treatment of fibrotic diseases.